Clinical Trial of a Home Safety Toolkit for Alzheimer’s Disease - Kathy J. Horvath (International Journal of Alzheimer's Disease, 2013)
This randomized clinical trial tested a new self-directed educational intervention to improve caregiver competence to create a safer home environment for persons with dementia living in the community. The sample included 108 patient/caregiver dyads: the intervention group (n=60) received the Home Safety Toolkit (HST), including a new booklet based on health literacy principles, and sample safety items to enhance self-efficacy to make home safety modifications. The control group (n=48) received customary care. Participants completed measures at baseline and at twelve-week follow-up. Multivariate Analysis of Covariance (MANCOVA) was used to test for significant group differences. All caregiver outcome variables improved in the intervention group more than in the control. Home safety was significant at P≤0.001, caregiver strain at P≤0.001, and caregiver self-efficacy at P=0.002. Similarly, the care receiver outcome of risky behaviors and accidents was lower in the intervention group (P≤0.001). The self-directed use of this Home Safety Toolkit activated the primary family caregiver to make the home safer for the person with dementia of Alzheimer's type (DAT) or related disorder. Improving the competence of informal caregivers is especially important for patients with DAT in light of all stakeholders reliance on their unpaid care.